Determination of Appropriate Furrow Length and Inflow Rate for Furrow Irrigation Practice on Smallholder Farmers at Omo Nada District for Maize (Zea Maize L.) Production - Etefa Tilahun Ashine; Minda Tadesse Bedane; Addisu Asefa Mengesha; Robel Admassu Lakewu; Hewan Tadesse Kebede (Air, Soil and Water Research)
An experiment was conducted on maize at Omo Nada district on a split-plot design with the objective of determining the optimum combination of furrow length and inflow rate under smallholder farmers’ conditions. The treatments include furrow lengths (10 m, 30 m, and 50 m) in the main plot and three inflow rates based on the maximum non-erosive inflow rates in the sub-plot. The data reveals that the plant height was affected ( p  < .01) by the variation of the furrow length, but the inflow rate had no significant effect ( p  > .05). The maximum and minimum plant heights of 224 and 209 cm were recorded at 30 and 50 m furrow length, respectively. Furrow length has an effect on the dry biomass of maize ( p  < 0.01), but there was no significant effect from the inflow rate. At a furrow length of 30 m, there was a maximum biomass production of 29,842 kg/ha, and the lowest dry biomass of 10,575 kg/ha was obtained at a 50 m furrow length. The grain yield of the maize crop was significantly ( p  < .01) affected by furrow length. The maximum average grain yield obtained was 9,811 kg/ha. The minimum grain yield of 5,576 kg/ha was obtained from a 50 m furrow length. There was a 43.17% yield increment between the 30 and 50 m furrow lengths. The interaction effect shows that L2Q1, L1Q1, and L2Q3 had the maximum correlation for grain yield, dry biomass, and water productivity, respectively. The maximum grain yield of 9,864 kg/ha and the minimum grain yield of 7,527 kg/ha were obtained at L2Q1 and L3Q3 treatments, respectively. It is evident to recommend that a combination of 30 m furrow length at a 0.99 L/s inflow rate could be effective for water management.